Occupational possibilities in a Brazilian mental health service: The perspective of users. (2nd January 2016) - Moraes Salles, Mariana; Simões Matsukura, Thelma
Abstract: Background : Psychosocial care centers (CAPS) are a type of service that redirects care to people with mental health problems in Brazil, de-emphasizing the asylum model and promoting the psychosocial model. Aim : To understand and analyze how CAPS contribute to the possibilities of occupational engagement of users. Methods : A qualitative research methodology was used and semi-structured interviews were conducted with 17 users of CAPS and 12 people from their social networks, totaling 29 interviews. Discourse analysis was used as a reference for data analysis. Results : CAPS provide opportunities, and, as users engage in the activities offered by CAPS, they can find the types of occupations that they want to perform and what they like to do, as their range of opportunities and access are expanded. However, promoting these occupational opportunities and choices in the community remains a challenge. Conclusions : CAPS have been able to help users improve their occupations in everyday life. Occupational therapists must build their clinical strategies in association with the opportunities offered by the health services and the community.